2021
DOI: 10.1155/2021/6643763
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin Theft Detection Based on Supervised Machine Learning Algorithms

Abstract: Since its inception, Bitcoin has been subject to numerous thefts due to its enormous economic value. Hackers steal Bitcoin wallet keys to transfer Bitcoin from compromised users, causing huge economic losses to victims. To address the security threat of Bitcoin theft, supervised learning methods were used in this study to detect and provide warnings about Bitcoin theft events. To overcome the shortcomings of the existing work, more comprehensive features of Bitcoin transaction data were extracted, the unbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It was found that the most effective results (accuracy: 97%) were achieved using Ada Boost, Support Vector Machine (SVM), and Random Forest (RF) classifiers, outperforming the other seven algorithms examined. In [37], the researchers focused on extracting more comprehensive features from Bitcoin transaction data to improve the detection of fraudulent activities. To address the issue of imbalanced data, measures were taken to equalize the dataset.…”
Section: Ethereum Fraud Detection Using Machine Learningmentioning
confidence: 99%
“…It was found that the most effective results (accuracy: 97%) were achieved using Ada Boost, Support Vector Machine (SVM), and Random Forest (RF) classifiers, outperforming the other seven algorithms examined. In [37], the researchers focused on extracting more comprehensive features from Bitcoin transaction data to improve the detection of fraudulent activities. To address the issue of imbalanced data, measures were taken to equalize the dataset.…”
Section: Ethereum Fraud Detection Using Machine Learningmentioning
confidence: 99%
“…S. Sayadi [42] proposed a solution to detect fraudulent transactions in cryptocurrency and proposed a technique to determine anomalies in electronic transactions of Bitcoin by machine learning, with high accuracy with k-mean and SVM. B. Chen et al [43] proposed machine learning-assisted solutions to detect Bitcoin theft transactions. The performance of five machine learning models (KNN, SVM, RF, Ad-aBoost, and MLP) is evaluated to identify the theft transactions in Bitcoin.…”
Section: Related Workmentioning
confidence: 99%
“…In the research conducted in 2021 on the Elliptic dataset [18], more generalized features were extracted to overcome the shortcomings of the previous studies. Moreover, by using oversampling methods, they tried to deal with the number of samples for each label in the imbalanced dataset.…”
Section: Machine Learning and Deep Learningmentioning
confidence: 99%